A dual ligand coordination strategy for synthesizing drum-like Co, N co-doped porous carbon electrocatalyst towards superior oxygen reduction and zinc-air batteries. (13th July 2021) - Huang, Kexin; Yang, Zhongyun; Liu, Ling; Yang, Xue; Fan, Youjun; Sun, Miaolan; Liu, Chengzhou; Chen, Wei; Yang, Jun
Abstract: We herein propose a dual ligand coordination strategy for deriving puissant non-noble metal electrocatalysts to substitute valuable platinum (Pt)-based materials toward oxygen reduction reaction (ORR), a key reaction in metal-air batteries and fuel cells. In brief, cobalt ions are firstly double-coordinated with proportionate 2-methylimidazole (2-MeIm) and benzimidazole (BIm) to obtain drum-like zeolitic imidazolate frameworks (D-ZIFs), which are then carbonized to output the final Co, N co-doped porous carbon (Co–N–PCD ) catalyst inheriting the drum-like morphology of D-ZIFs. The Co–N–PCD is featured by mesopores and exhibits superb electrocatalytic behavior for ORR. Impressively, the half-wave potential of Co–N–PCD catalysts is 0.886 V with finer methanol-tolerance and stability than those of commercial Pt/C. Additionally, a zinc-air battery assembled from the Co–N–PCD displays an open-circuit voltage of 1.413 V, comparable to that of commercial Pt/C (1.455 V), suggesting the potentials of Co–N–PCD in practical energy conversion devices. Graphical abstract: Image 1 Highlights: Drum-like ZIFs (D-ZIFs) are prepared by Co 2+, 2-methylimidazole and benzimidazole. Pyrolysis of D-ZIFs precursor yields Co, N, co-doped porous carbons (Co–N–PCD ). The porous channels allow facile diffusion of O2 to active species. Co–N–PCD exhibits high performance for ORR and in zinc-air batteries.